Diaphragmatic breathing for rumination syndrome: efficacy and mechanisms of action. Issue 3 (10th December 2015) - Halland, M.; Parthasarathy, G.; Bharucha, A. E.; Katzka, D. A.
Abstract: Background: While high resolution esophageal manometry combined with impedancometry has demonstrated that gastric pressurizations lead to rumination, the contribution of upper esophageal sphincter (UES) and esophagogastric junction (EGJ) function to rumination is unclear. Behavioral therapy with diaphragmatic breathing (DB) can reduce rumination. We aimed to evaluate the pressures in the stomach, EGJ and UES during rumination and the effects of DB augmented with biofeedback therapy. Methods: Sixteen patients with rumination were studied with manometry and impedancometry before and after a meal. The postprandial assessment comprised three periods: before, during, and after DB augmented with biofeedback therapy. Key Results: All patients had postprandial rumination, which was associated ( p < 0.001) with increased gastric pressure and reversal of the postprandial gastroesophageal pressure gradient from −4 (−43 to 18) before to 20 (7–79) mmHg during rumination. The EGJ pressure was lower ( p < 0.001) during gastric pressurizations that were associated with rumination vs those that were not. The UES also relaxed, almost completely, during rumination. Patients had a median (range) of 5 (2–10) rumination episodes before, 1 (0–2) ( p < 0.001) during, and 3 (1–5) after ( p < 0.001 vs during) diaphragmatic breathing. During manometry and impedancometry, DB was well‐tolerated and learned within 5 min. Diaphragmatic breathing increased EGJ pressure ( p < 0.001) and restored a negative gastroesophageal pressure gradient (−20 mmHg [−80 to 7]). Conclusions & Inferences: Diaphragmatic breathing aided with high resolution esophageal manometry is well‐tolerated, effective and averts the gastroesophageal pressure disturbance that leads to rumination. Abstract : Regurgitation in rumination syndrome occurs due to development of a flow permissive gastroesophageal pressure gradient resulting from greater gastric pressure and lower EGJ and UES pressure.